If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -7(m + -8) = 114 Reorder the terms: 2 + -7(-8 + m) = 114 2 + (-8 * -7 + m * -7) = 114 2 + (56 + -7m) = 114 Combine like terms: 2 + 56 = 58 58 + -7m = 114 Solving 58 + -7m = 114 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-58' to each side of the equation. 58 + -58 + -7m = 114 + -58 Combine like terms: 58 + -58 = 0 0 + -7m = 114 + -58 -7m = 114 + -58 Combine like terms: 114 + -58 = 56 -7m = 56 Divide each side by '-7'. m = -8 Simplifying m = -8
| Y=g(x-2) | | 1/9×=4 | | (X+3)4=y | | 9a^4x^5/4x/3a/2x | | 3(4-5n)=-78 | | 0.25k=3(-0.75k+3) | | 2v=v+13 | | 2b=b+88 | | 0.1(x-3)=1.1-0.25 | | b+10+7b=10 | | Z(2z+6)=3+z | | 4t-54=3t-9 | | 2n+6=48-5n | | -7n+10n=-33 | | (2(x^(1/2)))^2 | | 5t-92=t | | 1+7x+3x=21 | | 4p-32=p+31 | | 3m+5n=7 | | y=4y-30 | | -1=x-6+5 | | 2m=n-4 | | 21=4v-7v | | 9b-22=7b-16 | | -2(1-6r)=-2+4r | | 4v+6=41-3v | | 4s+14=2s+66 | | 3x^2+6x=168 | | p+p+64=180 | | -3(x-1)=-2x-3 | | 2a-21=a | | 12x-11y=23 |